HUBUNGAN PERILAKU MENYIKAT GIGI DENGAN TINGKAT KEBERSIHAN GIGI DAN MULUT PADA SISWA KELAS IV DAN V DI SDN 6 DLODPANGKUNG SUKAWATI TAHUN 2017 - I Made Budi Artawa; Pande Putu Nanda Pradipta (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2019)
Oral health is a fundamental part of overall health. The degree of health of a person or community is influenced by four factors, namely: environment, behavior, heredity, and health services. Plaque plays a role in the pathogenicity of caries and periodontal disease. The purpose of cleaning teeth is to remove plaque. Tooth brushing behavior is good and right that is done diligently, thoroughly and regularly. The results of the study by Pande Putu Nanda Pradipta concluded that there were no grade IV and V grade students at SD Negeri 6 Dlodpangkung, Sukawati who behaved brushing their teeth with both good and very good criteria. The level of dental and oral hygiene in grade IV and V students of SD Negeri 6 Dlodpangkung, Sukawati was classified as poor criteria. The purpose of this study was to determine the relationship between tooth brushing behavior and the level of dental and oral hygiene in grade IV and V SDN 6 Dlodpangkung Sukawati students in 2017. This type of cross sectional study, uses secondary data from Pande Putu Nanda Pradipta's research. Spearmen correlation test results obtained sig .: 0,000. Based on the results of this study it can be concluded that there is a relationship between tooth brushing behavior and the level of dental and oral hygiene in grade IV and V students of SDN 6 Dlodpangkung Sukawati in 2017.